Developmental Biology Protocols : Volume II - Tuan, Rocky S. (Totowa, NJ : Humana Press Inc., 2000., 2017)
INTRODUCTION -- ORGANOGENESIS -- ABNORMAL DEVELOPMENT AND TERATOLOGY -- SCREENING AND MAPPING OF NOVEL GENES AND MUTATIONS